Pengaruh Pengalaman, Kompetensi, Dan Tingkat Pendidikan Terhadap Skeptisme Profesional Melalui Profesionalisme - Mega Rianita Kartika; Avincennia Vindy Fitriana (Jurnal Riset Mahasiswa Akuntansi, 2026)
The purpose of this study is to examine the influence of experience, competence, and educational level on skepticism, both directly and indirectly through professionalism. The population of this study was all 85 employees at the West Java Provincial Inspectorate, whose identities were kept confidential and not to be published. The sampling technique used was saturated sampling, where the entire population was sampled. The data sources in this study were primary data obtained through the distribution of questionnaires related to the research variables and secondary data obtained from library studies and collecting data from literature and other sources related to the problem to be studied. This study employs a quantitative method with a causal design. Data analysis was performed using Structural Equation Modeling-Partial Least Square. The results indicate that experience does not influence professionalism, yet it significantly affects skepticism. Competence and educational level have a significant effect on professionalism, but they do not directly influence skepticism. Furthermore, professionalism is found to affect skepticism. Professionalism successfully mediates the influence of competence and educational level on skepticism; however, it fails to mediate the influence of experience on skepticism.